If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3(2n + 6) + -1n = 0 Reorder the terms: 7 + 3(6 + 2n) + -1n = 0 7 + (6 * 3 + 2n * 3) + -1n = 0 7 + (18 + 6n) + -1n = 0 Combine like terms: 7 + 18 = 25 25 + 6n + -1n = 0 Combine like terms: 6n + -1n = 5n 25 + 5n = 0 Solving 25 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 5n = 0 + -25 Combine like terms: 25 + -25 = 0 0 + 5n = 0 + -25 5n = 0 + -25 Combine like terms: 0 + -25 = -25 5n = -25 Divide each side by '5'. n = -5 Simplifying n = -5
| 8b-64a=8 | | 11x=286 | | 3(4x-6)+18= | | 2x-1=14-x | | 4z+3=6+2z | | 21-n+36= | | m+60=m+303 | | m+60=p+303 | | 6x-16=32 | | 5x+9=5+3x | | l=90(0+m)-3 | | 60=10p | | -7=117 | | 12-25+6=177 | | 3(x+2)-2(x-1)=7 | | y-21/3=-3 | | 85-79=27y-33y | | -n=5 | | x-6=34+34+3x | | x-6=34+34 | | -s=9 | | 2.3=x-5.9 | | x-6=34+x | | 39=z+51 | | 2d=5d-60 | | 5x+(-4)=36 | | 2D=0 | | -11=z-4 | | -2x-45=34+56 | | 4x-3+2x=8x-3-x | | -4(2p+4)-40=2(4p+4) | | -33+5y+3=2(4y-2)-2 |